ROLE OF PRIVATE EQUITY IN INDIAN ECONOMY - Sudhansu Sekhar Nanda (International Journal of Research Science and Management, 2015)
Private equity in India has perceived exponential growth in India during 2000-2008. India was once considered as a burning market for PE. Private equity investments have been a part of India’s emerging story for about a decade in which time we have seen a multitude of events that have shaped the investment climate in India. The country’s growing global stature, a far more open economy coupled with positive indications of reforms and perception of value residing within the fabric of the economy, encouraged investments into the country. The paper aims to find out how far India has been able to fulfill the expectations of PE in terms of return, Is India still one of the desired destinations of private equity. It also aims to find out how much private equity has contributed in the development of the country. Lastly, it will aim to assess the factors affecting private equity investment in the future.